THE POWER OF COMMUNITY ENGAGEMENT FOR DELIVERING CO-CREATION VALUE (Case: Paguyuban Sentra Industri Tempe Sanan-Malang Jawa Timur) - Mohamad Nasoha; Hubertina Karolina Ngarbingan; Ginta Ginting (Journal of the Community Development in Asia (JCDA), 2022)
ABSTRACT Building community engagement involving consumers, business actors, and others stakeholders as part of a marketing strategy for creating value co-creation has become a new phenomenon. This research provides a conceptual model of community-based action to assess its impact on value co-creation and how far it affects behavioral components in order to resolve the problem (intention and actual use). The suggested model can be used to conduct research to increase product purchase intent with high community involvement. Interviews and observations have been conducted at the Sentra Industri Tempe Sanan-Malang (East Java) to accurately execute the model, whose success is supported by the community's strength in the form of the association (Paguyuban). The research was conducted in July–August 2021 with the participation of 30 locals. The findings of the initial identification strongly support employing the suggested model in subsequent studies. Keywords: Actual Purchase, Behaviour, Community Engagement, Intention to repurchase, Value Co-creation.